ClCPI, a cysteine protease inhibitor purified from Cassia leiandra seeds has antifungal activity against Candida tropicalis by inducing disruption of the cell surface - Melo, Ivna R.S.; Dias, Lucas Pinheiro; Araújo, Nadine Monteiro Salgueiro; Vasconcelos, Ilka Maria Aria; Martins, Thiago Fernandes; Morais, Glaucia Almeida de; Gonçalves, José Francisco de Carvalho; Nagano, C. S.; Carneiro, Rômulo F.; Oliveira, José Tadeu A.Abreu (International Journal of Biological Macromolecules, 2019)
Infections caused by Candida tropicalis have increased significantly worldwide in parallel with resistance to antifungal drugs. To overcome resistance novel drugs have to be discovered. The objective of this work was to purify and characterize a cysteine protease inhibitor from the seeds of the Amazon rainforest tree Cassia leiandra and test its inhibitory effect against C. tropicalis growth. The inhibitor, named ClCPI, was purified after ion exchange and affinity chromatography followed by ultrafiltration. ClCPI is composed of a single polypeptide chain and is not a glycoprotein. The molecular mass determined by SDS-PAGE in the absence or presence of β-mercaptoethanol and ESI-MS were 16.63 kDa and 18.362 kDa, respectively. ClCPI was stable in the pH range of 7.0–9.0 and thermostable up to 60 °C for 20 min. ClCPI inhibited cysteine proteases, but not trypsin, chymotrypsin neither alpha-amylase. Inhibition of papain was uncompetitive with a Ki of 4.1 × 10 −7 M and IC 50 of 8.5 × 10 −7 M. ClCPI at 2.6 × 10 −6 M reduced 50% C. tropicalis growth. ClCPI induced damages and morphological alterations in C. tropicalis cell surface, which led to death. These results suggest that ClCPI have great potential for the development of an antifungal drug against C. tropicalis. © 2019
Keywords: Amylase; Antifungal Agent; Cassia Extract; Cassia Leiandra Extract; Chymotrypsin; Cysteine Proteinase Inhibitor; Mercaptoethanol; Papain; Polypeptide; Trypsin; Unclassified Drug; Antifungal Agent; Carbohydrate; Cysteine Proteinase Inhibitor; Reactive Oxygen Metabolite; Thiol Derivative; Chromatography, Affinity; Amazonas; Anti-fungal Activity; Candida Tropicalis; Cassia; Cassia Leiandra; Cell Death; Cell Surface; Controlled Study; Drug Purification; Drug Stability; Electrospray Mass Spectrometry; Enzyme Inhibition; Fungal Cell; Ic 50; Ion Exchange Chromatography; Molecular Weight; Nonhuman; Ph; Seed Plant; Electrophoresis, Polyacrylamide Gel; Rainforest; Thermostability; Ultrafiltration; Candida Tropicalis; Cell Membrane Permeability; Chemistry; Cytology; Drug Effect; Metabolism; Seed Plant; Temperature; Antifungal Agents; Candida Tropicalis; Carbohydrates; Cassia; Cell Membrane Permeability; Cysteine Proteinase Inhibitors; Hydrogen-ion Concentration; Inhibitory Concentration 50; Molecular Weight; Reactive Oxygen Species; Seeds; Sulfhydryl Compounds; Temperature